2021
DOI: 10.1140/epjd/s10053-021-00186-5
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental aspects of non-equilibrium plasmas in different regimes: fundamentals and selected applications

Abstract: This paper presents recent activities covering different plasma fields, from both theoretical and experimental point of views. An overview of the present interests of the scientific community is reported here. Starting from a brief description of the role of collisions in astrophysical plasmas, some fundamental aspects of gas discharges modelling, such as superelastic collisions and the basic concept of vibrational temperature, are discussed. Different plasma sources, as DBD and microwave discharges with their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 198 publications
(237 reference statements)
0
12
0
Order By: Relevance
“…The rate coefficients of electron impact reactions are obtained by solving Boltzmann's equation using BOLSIG+ 1 . Cross sections are taken from the Morgan, TRINITI, and Phelps databases [2][3][4] . What's more, the local field approximation is applied when calculating parameters, and the electron mean energy and electron transport coefficient are given as a function of reduced electric field.…”
Section: Computational Model Simulation Model and Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate coefficients of electron impact reactions are obtained by solving Boltzmann's equation using BOLSIG+ 1 . Cross sections are taken from the Morgan, TRINITI, and Phelps databases [2][3][4] . What's more, the local field approximation is applied when calculating parameters, and the electron mean energy and electron transport coefficient are given as a function of reduced electric field.…”
Section: Computational Model Simulation Model and Governing Equationsmentioning
confidence: 99%
“…DBD has the advantage of generating stable and uniform plasma, helping to avoid the transition to a high temperature arc with a constricted channel [2]. The production of oxidizing species in the DBD application of activating water for sanification such as hydrogen peroxide and ozone is efficient, giving the plasma antiseptic properties [3]. It is found that the externally enforced electric potential is able to generate a drift of the heavy species and electrons, leading to a charge density distribution which in turn creates distortions of the electric potential distribution in the bulk of the plasma [4].…”
Section: Introductionmentioning
confidence: 99%
“…[ 7,8 ] These compounds interact with bacteria, parasites, yeasts, molds, and viruses, damaging their structures and DNA, and eventually leading to their inactivation. [ 8–16 ]…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] These compounds interact with bacteria, parasites, yeasts, molds, and viruses, damaging their structures and DNA, and eventually leading to their inactivation. [8][9][10][11][12][13][14][15][16] Nowadays, several different techniques exist for nonthermal plasma production at atmospheric pressure. These include microwave plasmas, ultraviolet (UV) radiation, corona discharges, gliding arcs, and dielectric barrier discharge (DBD) plasmas.…”
mentioning
confidence: 99%
“…The assessed theoretical framework for the description of transient and stationary conditions of such plasmas is the state-to-state approach [5,6], where the quantum states of chemical species are treated independently in the master equations for the time evolution and characterized dynamically with state-specific cross sections and rate coefficients. The chemistry is coupled to the kinetics of free electrons and the internal and electron energy distributions are mutually affected.…”
Section: Introductionmentioning
confidence: 99%